Do Left-wing Voters Cycle more than Right-wing Voters? - Patrick Rérat; Emmanuel Ravalet (Findings)
Cycling is political when it comes to implementing cycling infrastructure. But what about riding a bike itself? Based on a representative survey in Switzerland, this paper shows the effect of political values on the frequency and reasons for cycling. All things being equal, Green voters cycle the most, especially for transport. Center and left-wing voters also cycle more than average. Right-wing voters are the least likely to cycle. However, the proportion of cyclists among their supporters is not negligible, which may indicate a dissonance with these parties' position on cycling as a mode of transport.